Interception of photosynthetically active radiation, growth and yield of grains in sunflower under doses of nitrogen - Lemainski, Liliani Elisa; Follmann, Diego Nicolau; Nied, Astor Henrique; Rossato, Rovani Marcos; Freiberg, Cristian Mateus; Brezolim, Eduardo (Revista Ceres, 2023)
The objective of the work was to evaluate the response of growth and production, the interception efficiency of photo-synthetically active radiation, the extinction coefficient, and the productivity components of sunflower in with the use of cover nitrogen doses in subtropical environments. The experiment was conducted at Santa Maria-RS, Brazil, where they were evaluated the leaf area index (LAI), interception efficiency (εi), and extinction coefficient (k) of photosynthetically active radiation (PAR), plant height (PH), chapter diameter (CPD), stem diameter (SD), the mass of one thousand achenes (MTA), and grain productivity (PROD) were evaluated. Nitrogen doses influenced the LAI only at 52 and 65 DAE, while the canopy interception efficiency (CIE) was influenced at 36, 42, 52, and 86 DAE. Therefore , for growth and production doses of cover N positively influence stem diameter and grain productivity. The application of cover nitrogen fertilizer linearly and positively affects the sunflower crop, and 160 kg ha-1 N. Interception efficiency of photosynthetically active radiation by the canopy and the leaf area index are positively influenced by the doses of nitrogen in the canopy. The extinction coefficient of the photosynthetically active radiation in sunflower decreases with the increasing dose of cover N.